Food security and nutrition- a systematic approach. (March 2021) - Wan, Andrew C.A.; Tai, Benjamin C.U.; Du, Chan
Abstract: Background: As highlighted in the FAO definition, nutritional quality is an important aspect of food security which has not been thoroughly addressed to date. There is an urgent need to measure the ability of alternative proteins to replace or supplement traditional sources in terms of both quality and quantity. Protein quality scores such as PDCAAS or DIAAS are available as quantitative measures of protein quality, incorporating both the digestibility of the protein and its content of indispensable amino acids. Scope and approach: This paper addresses the challenge of framing nutritional security in quantitative terms. The mass consumption of key protein-containing foods in Singapore was plotted against their respective PDCAAS scores, giving a snapshot of the protein quality profile for these major food types. For the purpose of analysis, protein quality was classified into four ranges in terms of PDCAAS values: >1, 0.8–1.0, 0.6 to 0.8 and < 0.6. A scaffold-based approach is proposed as a means to enhance consumer acceptance, and thus the demand and production of novel foods. Key findings and conclusions: The plot of mass of protein consumed vs protein quality provides an estimate of the nutritional shortfall for the different protein quality ranges, which can be supplemented by alternative proteins. The use of scaffolds in food product development offers benefits such as protein structuring, combining different food components and creating nutritional equivalents of traditional food products, all of which increase the level of consumer acceptance. Existing methods to make tissue engineering scaffolds can potentially be scaled up to fulfil the requirements for this new application. Highlights: Nutritional quality is an important aspect of food security which has not been thoroughly addressed. Nutrition can be linked to food security by plotting mass consumption of foods against their protein quality scores. The plot estimates the shortfall in local production for the different protein quality ranges. A scaffold-based approach is proposed as a quantitative means to meet the nutritional aspect of food security.